Factors associated with measles vaccination among children aged 12-59 months in Tambacounda commune, Senegal, in 2021 - Tidiane Gadiaga; Mouhamadou Faly Ba; Mbouna Ndiaye; Mamadou Sarifou Ba; Siré Sagna; Bayal Cissé; Babacar Gueye; Ousseynou Badiane; Elhadji Ba Konko Ciré; Jean Louis Abdou Ndiaye (Journal of Interventional Epidemiology and Public Health)
Introduction: To improve measles vaccination coverage among children in the commune of Tambacounda, a household survey was carried out among mothers and/or babysitters. The objective was to investigate factors related to immunization coverage at the first dose of measles and rubella (MR) vaccine in children aged 12 to 59 months.